Implementing a Four-Tier Diagnostic Test to Assess Elementary School Studentsâ on Electricity Concept - Marhadi, Hendri; Mulyani, Eva Astuti; widyanthi, Astri; Hermita, Neni (Proceedings of the UR International Conference on Educational Sciences, 2018)
This study reports on the implementing a four-tier test diagnostic instrument on magnetism concept, which has not been defined in the literature. It is an improved understanding of the two-tier test matters. The four-tier diagnostic test was focused on electricity concept. It was measured to 20 elementary school students. They were correctly trained on the preceding topics. The substantial corporate of the respondents was established to have an unfortunate kind and misconceptions of the subjects tested. We have already described that the test was able to investigate and categorize students into student conception of electricity concepts. Research result with four tier tests showed scientific conception 9 %, which was likely to have misconceptions 64 %, and the students were lack of knowledge the concept of 25 %, and had an error amounted to 2 %. The elementary school studentsâ inclined to be unwell aware among what they diagnosed and what they do not diagnosed. It might be determined that a Four-Tier Diagnostic Test which has previously been established be able to assess elementary school studentsâ conception on electricity concept.